Moringa oleifera is a Prominent Source of Nutrients with Potential Health Benefits - Islam, Zahidul; Islam, S. M. Rashadul; Hossen, Faruk; Mahtab-ul-Islam, Kazi; Hasan, Md. Rakibul; Karim, Rezaul (International Journal of Food Science, 2021)
Nowadays, the socioeconomic status has been changed a lot, so people are now more concerned about their life style and health. They have knowledge about the detrimental effects of synthetic products. That is why they are interested in natural products. Utilization of natural products of plant origin having fewer side effects has gained popularity over the years. There is immense scope for natural products that can intimate health benefits beyond traditional nutrients. Moringa oleifera is one such tree having tremendous nutritional and medicinal benefits. It is rich in macro- and micronutrients and other bioactive compounds which are important for normal functioning of the body and prevention of certain diseases. Leaves, flowers, seeds, and almost all parts of this tree are edible and have immense therapeutic properties including antidiabetic, anticancer, antiulcer, antimicrobial, and antioxidant. Most of the recent studies suggested that Moringa should be used as a functional ingredient in food. The aim of this review is to focus the use of Moringa oleifera as a potential ingredient in food products.